Penerapan Role Playing pada Materi Zakat untuk Meningkatkan Pemahaman Siswa di Kelas X E MAN 1 Cianjur - Nuroni, Asep (Edupedia Publisher, 2023)
This research aims to increase students' understanding, especially of the concept of zakat and the quality of the fiqh learning process by applying the Role Playing method to students in class X E MAN 1 Cianjur, Cianjur Regency. This research is Classroom Action Research (PTK) which was carried out in three cycles. Each cycle consists of planning, action, observation and reflection stages. The subjects of this research were teachers and students of class X E MAN 1 Cianjur. The data collection techniques used are documentation, observation, interviews and data validity tests, which in this research use triangulation, namely using a method that is carried out by comparing information or data in different ways. Based on the research results, it can be concluded that through the application of the Role Playing method it can improve students' understanding of the concept of zakat as well as the quality of the fiqh learning process in class X E MAN 1 Cianjur students.